Defining post‐traumatic stress disorder recovery in veterans: Benchmarking symptom change against functioning indicators. (28th December 2020) - Hinton, Mark; O'Donnell, Meaghan; Cowlishaw, Sean; Kartal, Dzenana; Metcalf, Olivia; Varker, Tracey; McFarlane, Alexander C.; Hopwood, Malcolm; Bryant, Richard A.; Forbes, David; Howard, Alexandra; Lau, Winnie; et al.
Abstract: Improved metrics of Post‐traumatic stress disorder (PTSD) treatment response that extend beyond a focus on symptom reduction to incorporate meaningful, patient‐centred indicators of functioning are needed in veteran populations. The aim of this study was to extend previous research by investigating whether indicators of functioning can successfully distinguish against symptom response categories derived from the Post‐Traumatic Stress Disorder Checklist (PCL‐5) pre‐ and post‐ PTSD treatment. Participants were 472 veterans receiving hospital‐based treatment for PTSD. In addition to the PCL‐5, measures included quality of life, social relationships, physical health and psychological distress. Four mutually exclusive, progressive response categories were used to define treatment response including: No Response, Response, Response and Below Threshold, and Remission. PTSD symptom reductions were associated with corresponding improvements in broader indicators of functioning. However, it was only when the magnitude of symptom reduction placed the individual in the 'Response and Below Threshold' category that improvement on functioning measures achieved levels indicative of a good end state. Traditional metrics of treatment 'response' in PTSD treatment do not necessarily indicate recovery on important functioning indicators. Only when an individual both responds to treatment and drops below threshold for probable disorder are they likely to report having meaningful levels of functioning.